Exploring the Antioxidant Potential and HPLC Profile of Fenugreek (Trigonella foenum-graecum L.) Seed Extracts - Hazel, Ahmed; Moumen, Ouahiba; Ould ali, Ouardia; Ouadjed , Hakim; Mecherour , Abdelaziz (The North African Journal of Food and Nutrition Research, 2025)
Background: The growing concerns regarding the adverse effects of synthetic antioxidants, coupled with documented detrimental outcomes of adverse drug reactions, such as increased morbidity, mortality, and hospitalization, as highlighted by several studies, have emphasized the necessity of natural alternatives. Therefore, medicinal compounds derived from plants are increasingly advocated for the management of various diseases, due to their perceived minimal side effects and extensive health benefits.Aims:  The objective of the present study was to investigate the potential of Trigonella foenum-graecum seeds as a natural source of bioactive compounds by assessing their antioxidant activity employing various in vitro assays. Additionally, this study aimed to determine the total phenolic, falconoid, and tannin contents in both hydroethanolic (50% v/v) and hydromethanolic (50% v/v) extracts. Furthermore, phytochemical profiling of the fenugreek seed extract was performed utilizing High-Performance Liquid Chromatography (HPLC).Materials and Methods: Following the extraction and quantification of total polyphenols, flavonoids, and tannins from hydroethanolic and hydromethanolic extracts, antioxidant activity was assessed employing three in vitro assays: the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging test, the ferric reducing antioxidant power (FRAP) assay, and the total antioxidant capacity (TAC) assay. Phenolic compounds were separated and identified using HPLC with Diode Array Detection (DAD). The obtained data were analyzed using SPSS software.Results: Phytochemical analysis revealed that the hydroethanolic extract exhibited a higher total polyphenol content (50.5 mg GAE/g) compared to the hydromethanolic extract (47.33 mgGAE/g). However, the evaluation of the antioxidant activity demonstrated that the hydromethanolic extract displayed the highest reducing power, as evidenced by the DPPH (IC50=314,53 mg/L), FRAP (21.49 mg AAE/g), and TAC (74.53 mg AAE/g) assays. Chromatographic characterization by HPLC identified six phytochemical compounds in the hydromethanolic extract of T. foenum graecum powder, which was obtained through maceration.Conclusions: In conclusion, Trigonella foenum graecum seeds represent a promising natural resource possessing significant biological activity. Their potent antioxidant properties render them valuable candidates for incorporation in pharmaceutical and cosmetic formulations to promote health and reduce damage induced by oxidative stress.Keywords: Trigonella foenum-graecum, Polyphenols, Antioxidant activity, Chromatography.
Keywords: Trigonella foenum-graecum; Polyphenols; Antioxidant activity; Chromatography